2016
DOI: 10.3892/mmr.2016.5912
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of complement system immunity in patients with myocardial infarction

Abstract: The aim of the present study was to evaluate differences in the expression of complement system genes, and serum levels of CH50, C3 and C4 in peripheral blood mononuclear cells from patients with myocardial infarction (AMI), stable angina pectoris (SA) and controls. A total of 100 patients with AMI, 100 with SA and 100 clinical controls were recruited in the present study. In each group, 20 randomly selected individuals were examined using whole human genome microarray analysis to detect the expression of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The average ages of the subjects ranged from 55±6.54 to 49.4±3.2 years. The diagnostic criteria of acute myocardial infarction were as follows: CT angiography showed that dissection diaphragm divided aorta into true lumen and false lumen ( 3 ). The diagnostic criteria of coronary artery stenosis were the pathological expansion of abdominal aorta exceeding 50% of normal blood vessel diameter ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average ages of the subjects ranged from 55±6.54 to 49.4±3.2 years. The diagnostic criteria of acute myocardial infarction were as follows: CT angiography showed that dissection diaphragm divided aorta into true lumen and false lumen ( 3 ). The diagnostic criteria of coronary artery stenosis were the pathological expansion of abdominal aorta exceeding 50% of normal blood vessel diameter ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…The change of serum enzymes included the sequence change of serum enzyme concentration or beginning at first and reducing later on, which was a typical evolution process of myocardial infarction. Six hours after on site, serum creatin phosphokinase (CK or CPK) appeared and reached a peak at 24 h, and disappeared after 48–72 h, with a positive rate of 92.7% ( 3 ). Before surgery, the patients were examined by coronary angiogram and diagnosed as acute myocardial infarction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that complement system is involved in a diverse range of pathological cardiac conditions. For example, Yan et al reported that the expression of CP and final path components was upregulated in PBMCs from patients with myocardial infarction, compared with stable angina pectoris and controls [4]. Hertle et al raised a conclusion from a large-sample cohort that the excessive AP activation would promote poor cardiovascular outcomes [5].…”
Section: Introductionmentioning
confidence: 99%